Pheromone trail following is not modulated by previous visit to food location, distance travelled, or travel direction in the ant Lasius niger - L.-A. Poissonnier; D. Winter; F.‑J. Olivera‑Rodriguez; C. Werneke; T. J. Czaczkes (Insectes Sociaux, 2026)
Ant foraging and recruitment often relies heavily on pheromone trails, and ants modulate pheromone trail deposition strategically. Ants are also known to modulate trail following depending on their own private information, such as the known location of the nest and their knowledge of food sources in the environment. Here we ask how a series of important context variables—distance from the nest, direction of travel, and prior food discovery—affects the fidelity of pheromone trail following in the black garden ant Lasius niger . Using both an open arena assay and a binary Y-maze design, we evaluated whether ants adjust their trail-following behaviour. Ants exhibited robust and consistent trail-following behaviour across all conditions. Surprisingly, we found no significant modulation by distance, travel direction, or recent experience. However, we observed that distance travelled before finding a pheromone trail significantly influenced subsequent walking patterns such as straightness, speed, and total distance travelled. These findings suggest that while L. niger trail-following behaviour is remarkably stable across contexts, locomotory traits remain plastic and context-sensitive. The decoupling of pheromone response from internal or external conditions highlights the need for further investigation into the mechanisms regulating individual foraging decisions in social insects.